Bus Rapid Transport System in Semarang City: Views of Current Users, Potential Users and Related Emission - Haryono Setiyo Huboyo; Wiwandari Handayani; Budi Prasetyo Samadikun; Didin Agustian Permadi (Universitas Diponegoro, 2022)
Abating the air emission related to the transportation sector by operation of the Bus Rapid Transport (BRT) system has been adopted in Indonesia. This study was conducted to obtain an overview of the implementation of BRT, the success of shifting private vehicles to BRT, and the number of emissions resulting from the operation of BRT. The study was conducted using a questionnaire and observations in BRT vehicles. A questionnaire survey was conducted randomly across Semarang sub-districts for 701 private vehicles consisting of cars and motorcycles in a parking lot. Questionnaires were distributed to BRT users in the waiting room and among those who left the BRT. The emission quantity is obtained from GPS observations installed in the BRT and quantified by the emission generation equation based on the bus speed. Even though they are not BRT users for daily activities, motorcycle users use BRT more frequently than private car users. For the private car and motorcycle users, the BRT coverage area is the first barrier to using the BRT system, followed by travel time (due to congestion and traffic jams). Based on current BRT users, the shifting of motorcycle users is far higher than private car users. About 30% of public transport users (besides BRT) shift to BRT users. The BRT emissions (CO and TSP) in the east-west corridor on weekdays and weekends are higher than those in the south-north corridor. Based on this study's results, the BRT application has not significantly reduced the use of private vehicles. Instead, shifting occurs from former public transport to BRT. BRT emissions are related to traffic route conditions and topography. BRT implementation needs to comprehensively consider social, economic and technical (infrastructure) aspects.